Engineering a more accessible world. - Simpson, R.C (IEEE Engineering in medicine and biology magazine)
Presents the results of the 2000 RESNA student scientific paper and student design competitions. The following topics are dealt with: feasibility of restoring shoulder function in high level tetraplegia; proactive balance while maintaining a stationary wheelie; excursion and stroke frequency differences between manual wheelchair propulsion and pushrim-activated power-assisted wheelchair propulsion; performance evaluation of command control algorithms for upper-extremity neuroprostheses; design of personal augmentation devices (exploratory play agents for children with severe disabilities); boccia ramp used by those with severe motor impairments; switch-activated ball thrower; 4-bar linkage mechanism for child prehensors; a potato wrapper for people with limited hand and finger coordination.